Effects of Computer Assisted Instruction (CAI) on Studentsâ€™ Achievement in Social Studies in Osun State, Nigeria - Adeyemi, B. A. (Richtmann Publishing, 2012)
The study investigated the effect of Computer Assisted Instruction (CAI) on Junior Secondary School Studentsâ€™achievement in Social Studies. The study equally examined the interaction effects of treatment of academic ability on studentsâ€™achievement in Social Studies. Simple random sampling was employed in selecting 160 students from four co-educationalpublic secondary schools in Osogbo and Ife Central Local Government Areas of Osun State, Nigeria. The study used a 2 x 2factorial analysis of ANOVA and three null hypotheses were tested. Four instruments were used namely: â€œSocial StudiesAchievement Testâ€ (SSAT) â€œComputer Assisted Instruction Guide for Social Studiesâ€ (AIGSS), â€œTeacher Operational Guide forSocial Studies Instructionâ€ (TOGSSI) and â€œStudentsâ€™ Academic Ability Testâ€ (SAAT) with reliability coefficients of 0.87, 0.79, 0.71and 0.78 respectively. Data Analysis was done by using Analysis of Covariance Procedure. The results indicated that there isno significant main effect of treatment (Computer Assisted Instruction and Conventional Methods) on student achievement inSocial Studies (F(1,153) = 0.415, P > 0.05). The result also revealed that there is significant main effect of academic ability onstudentsâ€™ achievement in Social Studies (F(1,153) = 7.852, P < 0.05). The high academic ability students were significantly betterthan the low ability students in their achievement in Social Studies. The findings further revealed that there is no significantinteraction effect of treatment and studentsâ€™ academic ability in their achievement in Social Studies (F(1,153) = 0.687, P > 0.05).Based on the findings of the study, recommendations were made among others, that conducive environment should be providedwith adequate facilities for Computer Assisted Instruction (CAI) as a mode of instruction to be effectively utilized in schools.